A novel EyePhone© App for improving adherence to glaucoma therapy - Leshno, Ari; Gaton, Dan; Singer, Reut; Eliasi, Elior; Vorobichik-Berar, Ofri; Madgar, Shiran; Stern, Ori; Jaber, Wasim; Kapelushnik, Noa; Skaat, Alon (Graefe's archive for clinical and experimental ophthalmology, 2021)
Purpose Despite advances in glaucoma treatment options, patient adherence and compliance remain very low. The EyePhone© App is a free non-commercial reminder application designed specifically for the needs of glaucoma patients. In this study, we evaluated its usefulness in improving adherence to medical treatment among glaucoma patients. Methods This is a prospective multicenter interventional study. Glaucoma patients were recruited from a tertiary center and a large community glaucoma service center. After a short explanation, the EyePhone© App was installed on their smartphone device, and the notifications for the current medical treatment were entered. After enrollment and at 1-month follow-up, subjects completed the Morisky Medication Adherence Scale (MMAS-8) and the Quality of Life and Glaucoma 17-item (GlauQOL-17) questionnaires for evaluation of adherence and QOL, respectively. Results In the study, 133 patients (71 men and 62 women) aged 62±15.5 years and using 2.0±0.9 IOP-lowering drugs participated. The proportion of highly adherent subjects improved from 29.3% (39/133) at baseline to 42.1% (56/133) at follow-up ( P < 0.001), and the proportion of poorly adherent subjects decreased from 29.3 (39/133) to 20.3% (27/133) at follow-up ( P = 0.012). QOL also improved, as evidenced by a significant increase in the GlauQOL-17 score ( P < 0.05). In a subgroup of patients for whom IOP measurements were available, IOP reduced by 0.92 mmHg ( P = 0.069). Conclusions Significant improvements in glaucoma adherence and QOL were achieved among poorly adherent glaucoma patients after 1 month of using the EyePhone© App.